THE IMPORTANCE OF MENTAL HEALTH (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Mental health plays a huge role to our life because well-being  is important, which has serious consequences for our life. This research paper explores the impact of mental health on everyday activity, preventative strategies for mental well-being, reviewing common mental health issues and ways in which society can promote mental well- being. According to the study, the results show that it is very crucial to talk more about mental health and support for people both at home and in the community.